Employers, the ghost at the feast? - Keep, E (Taylor and Francis, 2020)
The question addressed in this paper is why expanding Higher Education (HE) has become the default policy position in England. One answer concerns the reluctance by employers to train. The paper adopts an historical perspective on the policy reviews into this issue which have displayed a remarkable policy amnesia, employers have not been engaged. Consequently, successive governments have fallen back on expanding the HE sector as the main way to boost skill levels.